2017
DOI: 10.3390/molecules22060988
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uromodulin Levels in Prediction of Acute Kidney Injury in the Early Phase of Acute Pancreatitis

Abstract: In health, uromodulin is the main protein of urine. Serum uromodulin concentrations (sUMOD) have been shown to correlate with kidney function. Acute kidney injury (AKI) is among the main complications of severe acute pancreatitis (AP). No reports exist on sUMOD in patients with AP, including the diagnostic usefulness for early prediction of AP severity. We measured sUMOD during first 72 h of AP. Sixty-six adult patients with AP were recruited at the surgical ward of the District Hospital in Sucha Beskidzka, Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…Early prediction of AP severity is crucial to establish its proper management and, therefore, to avoid its serious complications and the resultant multiorgan dysfunction. Despite the assessment of local/systemic complications, it was recently demonstrated that Serum Soluble Fms-Like Tyrosine Kinase 1 (sFlt-1) [ 29 ], serum uromodulin [ 30 ], and serum neutrophil gelatinase-associated lipocalin (NGAL) [ 31 ] could serve as reliable early predictors of AP severity. Thus, a precise and detailed explanation of the pathophysiological and immunological processes and mechanisms of acute pancreatitis, including an investigation into different signal transduction pathways and a search for early biomarkers of the disease severity, remains a pressing issue.…”
Section: Discussionmentioning
confidence: 99%
“…Early prediction of AP severity is crucial to establish its proper management and, therefore, to avoid its serious complications and the resultant multiorgan dysfunction. Despite the assessment of local/systemic complications, it was recently demonstrated that Serum Soluble Fms-Like Tyrosine Kinase 1 (sFlt-1) [ 29 ], serum uromodulin [ 30 ], and serum neutrophil gelatinase-associated lipocalin (NGAL) [ 31 ] could serve as reliable early predictors of AP severity. Thus, a precise and detailed explanation of the pathophysiological and immunological processes and mechanisms of acute pancreatitis, including an investigation into different signal transduction pathways and a search for early biomarkers of the disease severity, remains a pressing issue.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies have found some new indicators that are associated with early renal injury, such as angiopoietin-2, which may be used as predictors of renal insufficiency [19]. And serum uromodulin is associated significantly with early renal injury of acute pancreatitis [20]. Zylka' study tested glomerular indicators in T2DM patients with early stages of chronic kidney disease and found that multiple biomarkers, such as serum cystatin C, urine IgG, transferrin, may be helpful in the assessment of early renal injury in T2DM patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Uromodulin (or Tamm-Horsfall protein) is a glycoprotein that is exclusively produced by renal tubular cells of the thick ascending part of the loop of Henle [65]. Recently, serum uromodulin concentrations have been shown to reflect the mass of remaining renal tissue and strongly positively correlate with GFR values across all stages of chronic kidney disease [108].…”
Section: The Markers Of Tubular Dysfunctionmentioning
confidence: 99%
“…Recently, serum uromodulin concentrations have been shown to reflect the mass of remaining renal tissue and strongly positively correlate with GFR values across all stages of chronic kidney disease [108]. In early phase of AP, serum uromodulin positively correlated with eGFR (independently of sex and age) and negatively with serum creatinine and cystatin C; however, the correlations were much weaker as compared to what has been observed in chronic kidney disease [65]. However, the diagnostic accuracy of serum uromodulin for the diagnosis of AKI complicating the early phase of AP (area under the ROC curve of 0.684) was lower than serum creatinine or cystatin C (Table 3) [65].…”
Section: The Markers Of Tubular Dysfunctionmentioning
confidence: 99%